PENGARUH KOLABORASI SMK DENGAN KELOMPOK MASYARAKAT DALAM PEMASARAN LULUSAN - Junaidah Junaidah; Ambiyar Ambiyar; Nizwardi Jalinus; Waskito Waskito (STKIP Persada Khatulistiwa Sintang, 2022)
The main issue that practically every nation in this hemisphere is dealing with is unemployment. With a relatively high unemployment rate, the Indonesian people also deal with this. The results of a survey by the Central Statistics Agency (BPS) as of August 2016, where there are more than 182.99 million Indonesian workers, and as many as 7.24 million people in Indonesia spread throughout the world and have not been accommodated by the world of work where SMK graduates are reported as the biggest contributor to the movement for the Indonesian nation. This study is part of the field of research and development. The Borg and Gall development model, which is divided into four stages—data collection, planning, development, and testing and validation—is referenced in this research and development. Field observations, interviews with study subjects, and the distribution of instruments in the form of questionnaires were all used to collect data. Based on the results of the study, it was concluded that the marketing collaboration program for SMK graduates with the gemeinschaft of mind community group was effective and could be an alternative in solving problems at the Vocational High School level.